Understanding the complex dynamics of transparency - Meijer, Albert (2013)
This article contributes to the growing body of literature on government by developing a model for studying the construction of transparency in interactions between governments and stakeholders. Building on theories about complex decision making, a heuristic model is developed that consists of a strategic, a cognitive, and an institutional perspective. To test the model's value, it is applied to two empirical cases: Dutch schools and the Council of the European Union. Applying the model to the school case provides insights into the connection between the introduction of transparency and the transformation in arrangements for safeguarding school quality. The case of the Council of the European Union highlights the role of transparency in the transformation of the council from a supranational to an intergovernmental body. The article concludes that the heuristic model, together with in-depth, longitudinal case studies, helps us understand government transparency in relation to broader transformations in the public sector. - Reproduced.
Keywords: Public administration